Dynamic Vibration Absorber with Negative Stiffness for Rotor System - Hongliang Yao; Zidong Chen; Bangchun Wen (Shock and Vibration)
To suppress the vibration of a rotor system, a vibration absorber combining negative stiffness with positive stiffness together is proposed in this paper. Firstly, the negative stiffness producing mechanism using ring type permanent magnets is presented and the characteristics of the negative stiffness are analyzed. Then, the structure of the absorber is proposed; the principles and nonlinear dynamic characteristics of the absorber-rotor system are studied numerically. Finally, experiments are carried out to verify the numerical conclusions. The results show that the proposed vibration absorber is effective to suppress the vibration of the rotor system, the nonlinearity of the negatives stiffness affects the vibration suppression effect little, and the negative stiffness can broaden the effective vibration control frequency range of the absorber.